Measles Trends, Immunization Coverage, and Surveillance Performance in Mataram City - Fatmi; Nurhidayati Nurhidayati; Deasy Irawati; Marisa Syavitri Dilaga (Media of Health Research, 2026)
This study examined trends in measles cases, immunization coverage, and surveillance performance in Mataram City, Indonesia, during 2023–2024. A descriptive-analytic design was applied using secondary data obtained from the Mataram City Health Office, the Ministry of Health, and the World Health Organization. Data on measles cases, booster immunization coverage, and population density were analyzed descriptively and using Spearman correlation. The results showed that measles cases decreased from 98 cases in 2023 to 50 cases in 2024, accompanied by an increase in booster immunization coverage from 53.8% to 62.1%. However, statistical analysis indicated no significant correlation between booster immunization coverage and measles cases (r = –0.133; p = 0.556) or between population density and measles cases (r = –0.253; p = 0.257). These findings suggest that factors beyond immunization coverage, such as surveillance quality and population mobility, may influence measles transmission. Strengthening immunization coverage to reach ≥95% and improving surveillance systems are essential strategies to enhance public health resilience.